The Implementation of Credentialing for First-Level Health Facilities of Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan Denpasar (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2016)
The implementation of credentialing program in JKN is different from the previous era, particularly for new medical facilities and medical provider of PT. Jamsostek and ASABRI. Therefore, this study aims at finding out the description associated with the process of credentialing implementation of the first-level health facilities from the perspective of PPK 1 and BPJS Kesehatan, Denpasar Branch. This research was conducted in January 2014 using qualitative approach. Data was collected through in-depth interviews to 11 medical facilities, as well as 2 executive credentialing teams from BPJS Kesehatan, Denpasar Branch. The subjects were selected purposively and the data was analyzed using thematic analysis. There are still some obstacles in the implementation of such credentialing program: there are still existing providers, especially TNI/Polri, which have the value below standard but are still contracted to serve JKN participants because the number is still relatively small. The new medical facilities have difficulty in self-assessment because there are many indicators that must be met, but the budget is limited. The study concludes that credentialing program has not yet fully applied the concept of managed care, thus regular monitoring to improve medical quality is needed.